Kajian Erosi Kualitatif Pada Budidaya Tanaman Karet Rakyat Usia 15 Tahun di Desa Lau Damak Kecamatan Bahorok, Kabupaten Langkat - Achmad William Halimas; Abdul Rauf; Mukhlis Mukhlis (Universitas Sumatera Utara, 2015)
Qualitative Erosion Studies on The Rubber Cultivation of The People Age 15 Years In the village of Lau Damak Bahorok subdistrict Langkat. The study aims to determine the qualitative erosion in the area of cultivation by using descriptive method with sampling technique based on stratified random sampling method. Research analyzing various parameters such as pH level of soil fertility, texture, Cation Exchange Capacity (CEC). Organic C, N-total, P-available, K can be exchanged (K-dd) and Bulk Density. The results show that the qualitative erosion that occurs in the area of rubber cultivation people aged 15 years in the village of Lau Damak Bahorok subdistrict Langkat cause terangkutnya nutrients P and K to the valley as well as the value of the levels of C-organic and N-total high value of land in the back caused by a number of existing litter above the soil surface.Required soil and water conservation efforts in the form of ground cover (cover crop) as well as the manufacture of terracing on slopes to prevent soil erosion.Key words : Descriptive, Qualitative erosion, Stratified Random Sampling.